2014
DOI: 10.1007/s00424-014-1441-2
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of nitric oxide-induced relaxation of porcine coronary artery: roles of the dimers of soluble guanylyl cyclase, phosphodiesterase type 5, and cGMP-dependent protein kinase

Abstract: Soluble guanylyl cyclase (sGC), phosphodiesterase type 5 (PDE5), and guanosine 3',5'-cyclic monophosphate (cGMP)-dependent protein kinase (PKG) are all dimeric. The present study was to determine the role of their dimeric status in nitric oxide-induced vasodilatation. In isolated porcine coronary arteries, after 20 h incubation with serum-free medium, serum-containing medium, or phosphate-buffered saline solution, the protein levels of the dimers of sGC, PDE5, and PKG were diminished while the monomer levels r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Recently, Gao, et al found an interesting mechanism for the regulation of sGC and PDE 5A activity, namely sulfhydryl-dependent dimerization formation. Heterodimers are formed by disulfide bonds of sGC protein α and β subunits, which activates sGC and its downstream pathway, causing the relaxation of blood vessels [ 28 ]. We found that NaHS at concentrations of 3, 50 and 300 μmol/L enhanced the sulfhydration of sGC β1, further proving that NaHS could inhibit sGC β1 activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Gao, et al found an interesting mechanism for the regulation of sGC and PDE 5A activity, namely sulfhydryl-dependent dimerization formation. Heterodimers are formed by disulfide bonds of sGC protein α and β subunits, which activates sGC and its downstream pathway, causing the relaxation of blood vessels [ 28 ]. We found that NaHS at concentrations of 3, 50 and 300 μmol/L enhanced the sulfhydration of sGC β1, further proving that NaHS could inhibit sGC β1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…In this mechanism, heterodimers are formed by disulfide bonds of sGC protein α and β subunits, activating sGC and its downstream pathway, and thus resulting in vasodilatory effects. Similar to sGC, the other key regulatory molecules in sGC/PDE/cGMP/PKG pathway, such as PDE are also constituted of two subunits, regulating its activity by the disulfide bond-dependent heterodimer formation [ 28 ]. Previous studies showed that H 2 S could regulate protein function via modifying the thiol group of protein (-SSH) [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, variations in sGC, PKG, and PDE protein contents were a focus of this study. There are two or three subunits in the protein structures of sGC, PKG, and PDE, and research has shown that the combined state of protein subunits, namely, the dimeric form, reflects the level of protein activity (25,42,47). In this study, we found that SO 2 could significantly increase cGMP concentration in the vascular tissue.…”
Section: Discussionmentioning
confidence: 53%
“…PKG has feedback regulation of sGC, can stimulate phosphodiesterase 5, can increase the hydrolysis of cGMP, and finally can reduce the concentration of cGMP. 26 PKG has two subtypes, PKG-1 and PKG-2, and they are distributed in different tissue. PKG-1 is mainly located in the cytoplasmic matrix and highly expressed in SMCs including vascular SMCs, platelets, fiber cells, and some white blood cells; little is expressed in vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%